2022
DOI: 10.1097/wnf.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suvorexant and Eszopiclone as Alternatives to Benzodiazepines for Treating Insomnia in Patients With Major Depressive Disorder

Abstract: ObjectivesWe investigated the utility of switching from benzodiazepines to suvorexant or eszopiclone to manage benzodiazepine-unresponsive insomnia in patients with major depressive disorder (MDD) in a randomized, open-label study.MethodsPatients with MDD who have insomnia symptoms (a score of >7 on the Insomnia Severity Index Japanese version [ISI-J]), who had received benzodiazepine treatment for more than 2 weeks (n = 18) were randomized to 4 weeks of suvorexant (20 or 15 mg/d) or eszopiclone (3 or 2 mg/d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…In an open-label, randomized study, 18 subjects with comorbid insomnia and major depressive disorder were investigated. Participants were currently taking various benzodiazepine hypnotics for at least 2 weeks but had residual insomnia (Insomnia Severity Index (ISI) score > 7) [ 33 ]. Subjects were randomized to receive either suvorexant or eszopiclone, and benzodiazepine dosage was reduced by half during the first 2 weeks of treatment and then discontinued.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an open-label, randomized study, 18 subjects with comorbid insomnia and major depressive disorder were investigated. Participants were currently taking various benzodiazepine hypnotics for at least 2 weeks but had residual insomnia (Insomnia Severity Index (ISI) score > 7) [ 33 ]. Subjects were randomized to receive either suvorexant or eszopiclone, and benzodiazepine dosage was reduced by half during the first 2 weeks of treatment and then discontinued.…”
Section: Resultsmentioning
confidence: 99%
“…Neither group reported rebound insomnia, and there were no changes in Pittsburgh Sleep Quality Index (PSQI) scores or increased adverse events compared to baseline. Depression and anxiety scores tended to improve, although this was only significant for reduced anxiety in the eszopiclone group [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…e Facility with ≥ 20 beds disorder (except for one case report [32]), anxiety disorder, or schizophrenia (except for one case report [33]) at the time of conducting our analyses. Very recently, Shigetsura et al reported a new finding that switching from BZD to suvorexant was associated with a significant improvement of insomnia in patients with major depressive disorder [34]. Overall, the findings published to date suggest that ORA is an effective and tolerable treatment option for insomnia in patients with a wide variety of psychiatric comorbidities, and that physicians may be becoming more familiar with their use in this setting.…”
Section: Discussionmentioning
confidence: 99%